Quality Of Student worksheet Based On Critical Thinking Skills In The Topic of Properties of Light - Tanjung, Erma Yanti; Panjaitan, Dwika Aulia; Ibrahim, Husna; Rambe, Khoirul Bariah; Alfina, Nadilla; Rianti, Tania Dwi (Indonesian Journal of Mathematics and Natural Science Education, 2024)
Critical thinking is the ability to analyze and evaluate information logically. This research aims to test the validity, practicality and improvement of critical thinking of fifth grade students at SD Negeri 106162 Medan Estate using student worksheet based on critical thinking skills on the properties of light. The research method used is research and development with the ADDIE model. The research results show that the student worksheet based on critical thinking skills has high validity, good practicality, and can improve students' critical thinking skills. It can be seen that the validity of the student worksheet which was developed using a validation sheet and the average validator is 86, so that the student worksheet based on critical thinking skills is included in the very valid category criteria. The practicality of the Student worksheet was measured using an educator questionnaire sheet and the average student response was 85.49 in the very practical category. The effectiveness of the student worksheet is measured by looking at changes in the pretest and posttest results, which show an increase in students' critical thinking skills at a percentage of 65% in the quite effective category. Based on the results of this research, it can be concluded that student worksheet based on critical thinking skills can be used as teaching material in student learning.